Layanan Pembelajaran Anak Slow Learner di Kelas 4 Sekolah Dasar - Chusna, Nuril Lailatul; Estu Harsiwi, Nova (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
Slow Learner is a condition of students with cognitive abilities that are below average but do not include disabilities, but slow learner children have difficulty achieving academic requirements in regular classes. Inclusive education is education provided to children with special needs and normal children in general so that they are able to achieve learning goals well according to the services provided. This research aims to determine the learning services provided by inclusive schools for slow learner children. The method used in this research is descriptive qualitative with a sample of one slow learner child in class 4 of SD Muhamadiyah 1 Bangkalan. SD Muhamadiyah 1 Bangkalan is a school that has implemented an inclusion program or is called an inclusive school. Based on the results of interviews and observations, inclusive school learning services for children with special needs are slow learner types, namely by having a special accompanying teacher for each child with special needs. In the learning process, special accompanying teachers collaborate with class teachers to guide slow learner children in achieving learning goals that are appropriate to the child's cognitive abilities. The formative and summative assessments given to regular and slow learner children are also differentiated. Slow learner children's report cards consist of academic report cards and student self-development report cards. This aims to convey personal development in the form of independence, social and attitude in the learning process at school. The above services provide development from a cognitive and affective perspective for slow learner children in class 4 at SD Muhamadiyah 1 Bnagkalan in the form of children who can read, write and understand the elements of reading stories and material but still need guidance from GPK.